Eighth IEEE International Conference on Pulsed Power 1991
DOI: 10.1109/ppc.1991.733284
|View full text |Cite
|
Sign up to set email alerts
|

Procyon Experiments Utilizing Explosively-formed Fuse Opening Switches

Abstract: This report was prepurcd tvsan account of work qsonaorcdby an agency of the [Jnilad Statm Ckwcrnmcnt Neither the [Jnited Sta(es Government nor any agency thereof, nor any of their cmpluyces, mukcs any wnrranty, express or implied, or asmumcsany Icgal liability or rcsportsi. bdity for Ihc uccuracy, cwr,pletwtcas, or uscfulncsnof any mformution, apparatus, product, or processdiscloacd, or rcprcscnls that IIS U.SCwould not mfrinpc privately owned rights. Rcfercncc hcrcm to any spccIfIc commercial product, prucws,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…First, we identified closing switch problems. The closing time of the Procyon-style switches [6] was strongly dependent on current, and the impedances of the switches were too large when they closed. Second, in an effort to correct the switch problem we inadvertently introduced a new breakdown problem in the Kapton insulation.…”
Section: A Causes Of Low Current Transfermentioning
confidence: 99%
“…First, we identified closing switch problems. The closing time of the Procyon-style switches [6] was strongly dependent on current, and the impedances of the switches were too large when they closed. Second, in an effort to correct the switch problem we inadvertently introduced a new breakdown problem in the Kapton insulation.…”
Section: A Causes Of Low Current Transfermentioning
confidence: 99%
“…From the cumulative data of 20 tests we found that the "Procyon-style" closing switches [9] had a standard deviation (a) from the mean delay of 39 ns at 13 kV. However, a increased with applied voltage across the switch, reaching 96 ns at 140 kV, the voltage at which the first switches were required to close in HEPP-ICE.…”
Section: ) Closing Switches and Jitter Controlmentioning
confidence: 97%
“…Timing of the closing switches is critical for achieving the correct current profile. From the cumulative data of 20 tests we found that the "Procyon-style" closing switches [9] had a standard deviation (a) from the mean delay of 39 ns at 13 kV. However, a increased with applied voltage across the switch, reaching 96 ns at 140 kV, the voltage at which the first switches were required to close in HEPP-ICE.…”
Section: ) Closing Switches and Jitter Controlmentioning
confidence: 97%